Analysis of Change in Body Composition in Diabetic Patients vs non-Diabetic Patients - Sharif, Nazia; Fazal, Imran; Alain, Noor (Pakistan Armed Forces Medical Journal, 2022)
Objective: To assess the difference in various parameters of body composition between the diabetic patients and non-diabetic controls at Pak Emirates Military Hospital Rawalpindi.Study Design: Comparative cross-sectional study.Place and Duration of Study: Medicine and Nutrition Department, Pak Emirates Military Hospital, Rawalpindi, from Jul 2018 to Mar 2019.Methodology: This study was conducted on 100 patients of non-insulin dependent diabetes mellitus under treatment in medicine department and matched controls from the community. Patients with type I diabetes or insulin dependents or having some other com or bid metabolic illness or autoimmune disease or malignancy were not included in the study. Parameters of body composition were measured by using the INBODY machine which works on the principle of electroimpedance.Results: Cases and controls were matched for age and gender. Hundred cases and hundred controls were recruited for the final analysis Mean age of the cases was 43.41 ± 2.231 years while controls were 43.46 ± 3.122 years. Mean BMI in cases was 29.32 ± 2.561while in controls was 25.62 ± 4.483. BMI, visceral fat and skeletal muscle fat were found statistically significant to be more in cases of non-insulin dependent diabetes mellitus as compared to the controls.Conclusion: This case control study revealed that diabetes significantly affects the body composition of the patients. It also affects other parameters like skeletal muscle mass and visceral fat. Routine screening of body composition should be made part of the diabetic clinics to pick these changes early and intervene accordingly.